Dietary ursolic acid improves health span and life span in male Drosophila melanogaster. (29th November 2018) - Staats, Stefanie; Wagner, Anika E.; Lüersen, Kai; Künstner, Axel; Meyer, Timo; Kahns, Anna K.; Derer, Stefanie; Graspeuntner, Simon; Rupp, Jan; Busch, Hauke; Sina, Christian; Ipharraguerre, Ignacio R.; et al.
Abstract: The health and life span of Drosophila melanogaster are partly determined by intestinal barrier integrity, metabolic rate as well as stress response and the expression of longevity‐associated genes, depending on genetic and dietary factors. Ursolic acid (UA) is a naturally occurring triterpenoid exhibiting potential antimicrobial, anti‐inflammatory, and antiobesity activity and counteracting age‐related deficits in muscle strength. In this study, UA was dietarily administered to w 1118 D. melanogaster which significantly elongated the health and life span of males. Spargel ( srl ) is the Drosophila orthologue of mammalian peroxisome proliferator‐activated receptor‐gamma coactivator 1 α(PGC1α), an important regulator of energy homeostasis and mitochondrial function. Our results indicate that the health‐promoting effect of UA, demonstrated by a significant increase in climbing activity, occurs via an upregulation of srl expression leading to a metabolic shift in the fly without reducing fecundity or gut integrity. Moreover, UA affected the flies' microbiota in a manner that contributed to life span extension. Srl expression and microbiota both seem to be affected by UA, as we determined by using srl‐ mutant and axenic flies. © 2018 BioFactors, 45(2):169–186, 2019